Production and characterization of a thermostable antifungal chitinase secreted by the filamentous fungus Aspergillus niveus under submerged fermentation - Alves, Thais Barboni [UNESP]; Oliveira Ornela, Pedro Henrique de [UNESP]; Cavalcanti de Oliveira, Arthur Henrique [UNESP]; Jorge, Joao Atilio; Souza Guimaraes, Luis Henrique [UNESP] (Springer, 2018)
The filamentous fungus Aspergillus niveus produced extracellular antifungal chitinase when cultured under submerged fermentation (SbmF) using crab shells as the carbon source. Maximal chitinase production was achieved at 192 h of cultivation using minimal medium containing 1% chitin. The enzyme was purified 1.97-fold with 40% recovery by ammonium sulfate precipitation and Sephadex G-100 gel filtration. The molecular mass was estimated to be 44 kDa by both 12% SDS-PAGE and Sepharose CL-6B gel filtration. Maximal A. niveus chitinase activity was obtained at 65 degrees C and pH 5.0. The enzyme was fully stable at 60 degrees C for up to 120 min and the enzymatic activity was increased by Mn2+. In the presence of reducing and denaturing compounds, the enzyme activity was not drastically affected. The chitinase was able to hydrolyze colloidal chitin, azure chitin, and 4-nitrophenyl N-acetyl-beta-D glucosaminide; for the latter, the K-0.5 and maximal velocity (V-max) were 3.51 mM and 9.68 U/mg of protein, respectively. The A. niveus chitinase presented antifungal activity against Aspergillus niger (MIC = 84 mu g/mL), A. fumigatus (MIC = 21 mu g/mL), A. flavus (MIC = 24 mu g/mL), A. phoenicis (MIC = 24 mu g/mL), and Paecilomyces variotii (MIC = 21 mu g/mL). The fungus A. niveus was able to produce a thermostable and denaturation-resistant chitinase able to inhibit fungal development, signaling its biotechnological potential.
Keywords: Aspergillus niveus; Antifungal activity; Chitin; Chitinase; Fungal hydrolases